Pain in axial spondyloarthritis: role of the JAK/STAT pathway - Selmi, Carlo; Chimenti, Maria Sole; Novelli, Lucia; Parikh, Bhumik K.; Morello, Francesca; de Vlam, Kurt; Ciccia, Francesco (Frontiers in Immunology, 2024)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that is characterized by new bone formation in the axial musculoskeletal system, with X-ray discriminating between radiographic and non-radiographic forms. Current therapeutic options include non-steroidal anti-inflammatory drugs in addition to biological disease-modifying anti-rheumatic drugs that specifically target tumor necrosis factor-alpha (TNFα) or interleukin (IL)-17. Pain is the most critical symptom for axSpA patients, significantly contributing to the burden of disease and impacting daily life. While the inflammatory process exerts a major role in determining pain in the early phases of the disease, the symptom may also result from mechanical and neuromuscular causes that require complex, multi-faceted pharmacologic and non-pharmacologic treatment, especially in the later phases. In clinical practice, pain often persists and does not respond further despite the absence of inflammatory disease activity. Cytokines involved in axSpA pathogenesis interact directly/indirectly with the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling cascade, a fundamental component in the origin and development of spondyloarthropathies. The JAK/STAT pathway also plays an important role in nociception, and new-generation JAK inhibitors have demonstrated rapid pain relief. We provide a comprehensive review of the different pain types observed in axSpA and the potential role of JAK/STAT signaling in this context, with specific focus on data from preclinical studies and data from clinical trials with JAK inhibitors.